2004
DOI: 10.1177/039139880402701111
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Alterations in Glycerol Preserved Rat Aortic Allografts

Abstract: Glycerol preservation is an effective method for long-term preservation of skin allografts and has a potential use in preserving arterial allografts. We evaluated the effect of glycerol concentration and incubation period on vessel-wall integrity of rat aortic allografts. No significant differences were measured in breaking strength (2.3 ± 0.3 N) and bursting pressure (223 ± 32 kPa) between standard glycerolized and control segments (1.7 ± 0.3 N, 226 ± 17 kPa). Isometric tension measurements showed complete la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
1
11
0
11
Order By: Relevance
“…Each sample was cut open longitudinally and dehydrated in graded solutions of glycerol/saline of 50, 75, 87 and 100% for 1 h each to clear the specimen, permitting an accurate light scattering measurement. Note that glycerol treatment did not cause distortion of the tissue’s shape or structure [51,53]. The samples were then unfolded and SALS measurements were conducted over the entire tissue by raster scanning.…”
Section: Methodsmentioning
confidence: 99%
“…Each sample was cut open longitudinally and dehydrated in graded solutions of glycerol/saline of 50, 75, 87 and 100% for 1 h each to clear the specimen, permitting an accurate light scattering measurement. Note that glycerol treatment did not cause distortion of the tissue’s shape or structure [51,53]. The samples were then unfolded and SALS measurements were conducted over the entire tissue by raster scanning.…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vitro experiments in our laboratory showed that this protocol resulted in optimal glycerol preservation of arterial allografts [18] .…”
Section: Preparation Of Glycerol-preserved Allograftsmentioning
confidence: 87%
“…The fact that glycerol preservation results in a tissue matrix without living cells diminishes immunogenicity of the graft. Previous experiments in our laboratory demonstrated that glycerol preservation of the rat aorta preserves the biomechanical characteristics and architecture of the vessel wall [18] .…”
Section: Introductionmentioning
confidence: 87%
“…LPPs were measured in accordance with the method of Basu et al 4 and Fahner et al 9 One end of the laser-treated carotid segment was sealed by ligation, and the vessel lumen was filled with 0.9% saline solution containing MB as a visual indicator at 99 mL/h. The other end was ligated around a hollow needle that was connected to a rate-controlled syringe infusion pump and a pressure controller (Braun Medical, Melsungen, Germany) through an interposed T-valve.…”
Section: Methodsmentioning
confidence: 99%